Determinan Aktivitas Fisik Orang Dewasa Pekerja Kantoran di Jakarta Tahun 2018 - Dinanti Abadini; Caroline Endah Wuryaningsih (Jurnal Promosi Kesehatan Indonesia, 2019)
Background: Benefits of adult physical activity for health maintenence and disease prevention have been extensively documented. Sedentary occupation believed as a factor which contributes to office workers insufficient physical activity. Jakarta was the province with the highest proportion of insufficient physical activity (44.2%). Majority workers in Jakarta were as office workers. This study aims to analyze determinant factors influence to physical activity of office workers in Jakarta City.Method: The research was conducted in quantitative method using a cross-sectional approach. A total of 174 Jakarta’s office workers have participated in online questionnaire by submitting response via website. The questionnaire to measure the level of physical activity used in this study is Global Physical Activity Questionnaire (GPAQ) which is developed by WHO. This questionnaire measures a lot of time spent on physical activity at work, travel (transportation) and also free time in one week which is then converted into units of metabolic equivalents (METs). These METs scores were then categorized to be quite physically active (METs ≥ 600) or less physically active (METs <600).Results: The study found that 59% of office worker who work in Jakarta had insufficient physical activity. Statistical anlysis revealed that male, friends support and low perceived barriers were the factors influenced sufficient physical activity of office workers. Health intervention and promotion which intend to reduce perceived barriers, and increase perceived benefits of doing physical activity, encourage friends to support to increase physical activity of workers are needed to be developed. In addition, special attention should be given to female office workers in order to increase their participation in physical activity.